2012
DOI: 10.6000/1927-5129.2012.08.01.29
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Major Mechanism of Global Warming and Climate Change

Abstract: Abstract:In a two-year study ten commercial date palm varieties were evaluated. The varieties showed varying response to Rhynchophorus ferrugineus Oliv; some varieties suffered heavy infestation while others indicated tolerance against R. ferrugineus. The most tolerant varieties with less infestation percentage against R. ferrugineus were Muzawati (8%) followed by Pathri (12%), Thothar (15%), Khar and Shakri (16%) respectively. The varieties which suffered high infestation rate were Karbalain, Dhedhi, Fasli, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…When one of the objects moves to a new distance Rn, Equation 1 becomes 2 n n Mm F G R = ( 2 ) This is possible as any transient perturbing force of sufficient magnitude can alter the orbital distance R to Rn. For instance, it was shown that the strong Sumatra quake of December 26, 2004 and its giant tsunami moved the moon by increasing the gravitational force resulting to the increased tilt of the planet earth as the moon receded (Rivera, 2011;Rivera & Khan, 2012). Hence, transient gravitational weakening can occur due to massive quakes.…”
Section: Theoretical Foundation and Extended Newtonian Gravitationmentioning
confidence: 99%
See 4 more Smart Citations
“…When one of the objects moves to a new distance Rn, Equation 1 becomes 2 n n Mm F G R = ( 2 ) This is possible as any transient perturbing force of sufficient magnitude can alter the orbital distance R to Rn. For instance, it was shown that the strong Sumatra quake of December 26, 2004 and its giant tsunami moved the moon by increasing the gravitational force resulting to the increased tilt of the planet earth as the moon receded (Rivera, 2011;Rivera & Khan, 2012). Hence, transient gravitational weakening can occur due to massive quakes.…”
Section: Theoretical Foundation and Extended Newtonian Gravitationmentioning
confidence: 99%
“…Unknown to many, the earth can perturb the moon in its orbit during massive quakes (Rivera, 2011). It is also possible that strong and long-lasting moonquakes can perturb the earth.…”
Section: Seismic-perturbed Gravitation -The Problem Of Geo-astronomicmentioning
confidence: 99%
See 3 more Smart Citations